ScrambleSQL: A Novel Drag-and-drop SQL Learning Tool - Phewkum, Chanapat; Kaewchaiya, Jittakan; Kobayashi, Kazuki; Atchariyachanvanich, Kanokwan (My University, 2019)
Structured Query Language (SQL) is a standard language for forming queries to access relational database systems, e.g. create table, as well as read, update, and delete data from the database. Thus, it is commonly taught in computer science classes. Technology growth helps developers to create many SQL tools which encourage students to learn effectively. Although many SQL learning tools have been developed, they are not suitable for some users who prefer to use a tablet for learning SQL, because the existing tools were not developed for a touchscreen device. Thus, we developed prototype ScrambleSQL, optimized for tablets. The purpose was to enhance learning, speed up SQL command writing and allow users to practice SQL commands anywhere and anytime, with the internet. We tested undergraduate students from an Information Technology program. They wrote SQL commands by ScrambleSQL and then completed a questionnaire. The participants were satisfied with its screen, learning and system capabilities. ScrambleSQL reduced typing errors and helped novice users to learn SQL commands with the provided keywords. In addition, the participants enjoyed learning with ScrambleSQL.
Keywords: computer-aided instruction; drag-and-drop interface; SQL learning